Prevalence of Meticillin-Resistant Staphylococcus aureus Colonisation amongst Residents in Maltese Nursing Homes - Borg, Ryan Fredi; Gatt, Christine; Borg, Michael A (International Journal of Infection Control, 2018)
Since the 1960’s, meticillin-resistant Staphylococcus aureus (MRSA) has become a major pathogen with ever-increasing incidence rates of hospital-acquired and community-acquired infections. Malta has currently one of the highest rates of hospital-acquired and community-acquired infections in Europe. In addition, reports have estimated community carriage at more than 8%. MRSA carriage in homes for the elderly is very important because these residents are often hospitalized and therefore serve as a source of transmission.The aims of this study were to establish the prevalence of MRSA nasal carriage amongst residents in nursing homes in Malta, to determine their antibiotic susceptibility and to determine the significance of specific risk factors found in the literature.Nasal swabs were taken from 397 randomly chosen residents in 10 governmental nursing homes. A short questionnaire including possible risk factors reported to be associated with MRSA nasal carriage was also filled.MRSA carriage amongst nursing home residents was 19.4% (95% CI 17.6 – 21.2%) ranging from 0% to 25% amongst the nursing homes studied. Logistic regression analyses indicated that previous hospital admission was the only risk factor that was found to be significantly (OR: 1.956, p: 0.011; 95CI 1.163 - 3.290) associated with MRSA nasal colonization amongst nursing home residents.A high carriage rate of MRSA was identified in Maltese nursing care residents which can contribute to maintaining MRSA incidence in hospitals. Possible interventions include screening of these patients when they are admitted to an acute care facility and possible decolonization attempts in the nursing homes.